Central Banks Under German Rule During World War II: The Case of Norway - Harald Espeli (Norges Bank, 2012)
Until the German invasion of Norway 9 April 1940 the Norwegian central bank had been one of the most independent in Western Europe. This article investigates the agency of the Norwegian central bank during the German occupation and compares it with central banks in other German occupied countries. The Norwegian central bank seems to have been more accommodating to German wishes and demands than the central banks in other German occupied countries in Western Europe.
hdl:11250/2496836
Keywords: H56; N44; N94; 330; Norway; world war II; german occupation; central banks